Instructional Psychology for School Counsellors - Osborne, John W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes a systems approach to instructional psychology which can be used by school counsellors as a basis for diagnosis and remediation in the classroom.The interrelationships of the four components of a basic teaching model are emphasized. Selected aspects of each component, which are important for effective instruction, are discussed.